2010
DOI: 10.1097/bpo.0b013e3181c6c363
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Results of Lateral Band Translocation for the Correction of Swan Neck Deformity in Cerebral Palsy

Abstract: The long-term result of lateral band translocation is disappointing in our series, and it should not be advocated as a procedure with long-lasting success in patients with cerebral palsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Following lateral band translocation (rerouting), de Bruin and colleagues reported that correction was successful for 84% of the operated fingers at 1-year follow-up and 60% after 5 years. 18 Carlson and colleagues reported improvement in dynamic swan-neck deformity averaging 32 degrees for the central slip tenotomy method. 19 No swan-neck deformity was worse than its preoperative state, and no patient developed boutonniere deformity.…”
Section: Discussionmentioning
confidence: 99%
“…Following lateral band translocation (rerouting), de Bruin and colleagues reported that correction was successful for 84% of the operated fingers at 1-year follow-up and 60% after 5 years. 18 Carlson and colleagues reported improvement in dynamic swan-neck deformity averaging 32 degrees for the central slip tenotomy method. 19 No swan-neck deformity was worse than its preoperative state, and no patient developed boutonniere deformity.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports of single lateral band transfers to treat PIP joint hyperextension and swan-neck finger deformities in association with rheumatoid arthritis and cerebral palsy [7,13,14,18,22,24,25,28]. Further variations in technique include use of the radial lateral band, attachment of the lateral band to the bony proximal phalanx, use of a bone anchor [10], rerouting the lateral band across the volar aspect of the PIP joint to the contralateral side of the digit, and use of a free tendon graft (the so-called spiral oblique retinacular ligament reconstruction) [23].…”
Section: Discussionmentioning
confidence: 99%
“…Further variations in technique include use of the radial lateral band, attachment of the lateral band to the bony proximal phalanx, use of a bone anchor [10], rerouting the lateral band across the volar aspect of the PIP joint to the contralateral side of the digit, and use of a free tendon graft (the so-called spiral oblique retinacular ligament reconstruction) [23]. The results have been generally favorable in the short term, but recurrent finger deformities with longer follow up have been reported [7]. Progressive pannus formation in rheumatoid arthritis will lead to attenuation of soft tissues and joint deformity with a potential for relapsing instability [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1C). 1,19 Double lateral band transfer: The extensor apparatus was exposed through the dorsal incision. The radial and ulnar lateral bands were dissected from the central tendon approximately 1 cm proximal and 1 cm distal to the PIP joint leaving the proximal and distal ends intact.…”
Section: Surgical Techniquesmentioning
confidence: 99%